Awareness of Nigerian Mothers on the Risk Factors, Prevention and Management of Seizures in Newborns - Olarinde, Oluwatosin; Ajibade, Bayo Lawal; Attah, Cynthia Adaku; Akingbade, Oluwadamilare (Iranian Journal of Child Neurology, 2023)
Objectives The study aimed to assess the awareness of mothers on the risk factors, prevention, and management of seizures in newborns. Materials & Methods This descriptive cross-sectional study was conducted on 359 mothers using simple random sampling. The data were collected using questionnaires that included general awareness, awareness of the causes, risk factors, prevention, and management. The data collected were analyzed using frequencies and percentages. Null hypotheses were tested using chi-square at 0.05 level of significance Results Two hundred seventy-four mothers (76.3%) had high awareness of seizures in newborns, thirty-four (9.5%) had average awareness, and fifty-one (14.2%) had low awareness. Two hundred and seventythree mothers (76%) had high awareness of the risk factors, and eighty-six (24%) had low awareness, meaning that although some respondents had misconceptions, awareness of the risk factors and causes was good. Two hundred twenty-three (62.1%) respondents had high awareness of preventing seizures in newborns, while 136 (37.9%) had low awareness. The awareness of respondents on managing seizures in newborns is positive, as 291 (81.1%) had high awareness of managing seizures in newborns, while sixty-eight (18.9%) had low awareness. There was a significant relationship between age (p =0.000), marital status (p=0.018), level of education (p =0.000), and awareness of risk factors of seizures in the newborn Conclusion A high awareness of neonatal seizures was found among mothers because of their high educational level, although some still had some misconceptions. Improving maternal neonatal seizure awareness and appropriate educational interventions to correct misconceptions are needed.